The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21470/1678-9741-2019-0181
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Utilization and In-Hospital Outcomes of Surgical Aortic Valve Replacements in Spain, 2001-2015

Abstract: Objective: The aims of this study were to examine the incidence and in-hospital outcomes of surgical aortic valve replacement (SAVR) and to identify factors associated with in-hospital mortality (IHM) among patients according to the type of implanted valve used in SAVR. Methods: We performed a retrospective study using the Spanish National Hospital Discharge Database, 2001-2015. We included patients who had SAVR listed as a procedure in their discharge report. Results: We identified 86,578 patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The observed mortality rate has outperformed the predicted mortality rate by nearly 50% in 2016–2018. The mortality rate in the United Kingdom has further reduced since the last report ( 13 ) and other reports in the literature ( 9 , 14 ).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The observed mortality rate has outperformed the predicted mortality rate by nearly 50% in 2016–2018. The mortality rate in the United Kingdom has further reduced since the last report ( 13 ) and other reports in the literature ( 9 , 14 ).…”
Section: Discussionmentioning
confidence: 86%
“…Our study demonstrated that SAVR remains an effective treatment with low mortality for patients with isolated aortic valve disease. The number of patients with high-risk, octogenarians undergoing isolated SAVR, and those requiring redo surgery has reduced in recent years, likely due to the (13) and other reports in the literature (9,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the predictors for the 30-day composite endpoint, there were important differences between first-time and repeat AVR procedures. Although female sex, age, congestive heart failure (CHF), coronary artery disease, cerebrovascular disease, and renal function were previously documented to impact first-time SAVR patients' adverse clinical outcomes [31,32] , these were not identified in the present r-AVR study. Similarly, pulmonary hypertension, renal function, and diabetes had been found to be predictors of post-TAVR adverse clinical outcomes in a prior study [33] .…”
Section: Discussionmentioning
confidence: 75%